(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article investigates the functional correspondence between two distinct grammatical features: Uzbek auxiliary verbs (ko’makchi fe’llar) and English light verbs (LVs). While these features originate in separate language families (Turkic and Germanic), they demonstrate striking parallels in their structural role, which is the grammaticalization of semantic content related to aspect, duration, and change of state. By examining common English LVs such as go, keep, and turn against their functional counterparts in Uzbek AV structures, this analysis reveals a shared cognitive strategy for creating complex, nuanced predicates without relying on fully lexical verbs.